Experimental study on the effect of injection pressure ratio on the propagation characteristics of hydrogen rotating detonation waves. Issue 10 (11th July 2022) - Wu, Minxuan; Bai, Qiaodong; Han, Jiaxiang; Zhang, Shijian; Cui, Shengnan; Chen, Hao; Weng, Chunsheng
Abstract: This study aimed to evaluate the effects of the ratio of air injection pressure to hydrogen injection pressure ( p R = p A / p H ) on the propagation characteristics of rotating detonation waves (RDWs) and the working range of continuous rotating detonation engines (CRDEs). To this end, experiments were conducted under different injection pressure ratios and air mass flow rates with hydrogen as the fuel and air as the oxidant. The results reveal that RDWs can propagate in a stable manner when the injection pressure ratio is 0.67–1.7; however, RDW propagation is unstable when the injection pressure ratio is 0.51–0.67 and 1.7–2.03. The formation of unstable detonation waves may be attributed to the long response times at low pressures and the poor mixing effect of hydrogen and air. Furthermore, under an injection pressure ratio of 2.08–3.09, CRDE initiation failed. As the air mass flow rate increased, the range of the injection pressure ratio increased and the CRDE operated in a stable manner. In addition, the RDW velocity first increased and then decreased as the injection pressure ratio increased. Notably, under an air injection pressure of 3.6 bar, the rotation direction of the RDW changed during propagation. Abstract : To study the effects of the ratio of air injection pressure to hydrogen injection pressure ( pR = pA / pH ) on the propagation characteristics of rotating detonation waves (RDWs) and the working range of continuous rotating detonation engines (CRDEs), experiments were conducted under different injection pressure ratios and air mass flow rates with hydrogen as the fuel and air as the oxidant.